Teachers’ Perception for the Issue with Effective Science Teaching and Learning - Dahal, Bishnu Kumar (Ganeshman Darpan, 2022)
This study aimed to find out how secondary school teachers perceived successful science instruction and learning. A descriptive survey design was therefore employed in the study. The sample size for the study included 14 secondary-level science teachers who worked in five public schools in the districts of Kathmandu, Lalitpur, and Bhaktapur. A structured questionnaire of the 5-point Likert type designed by the researcher was the tool used to collect data. After the instrument was validated, the reliability coefficient, which was calculated using Cronbach alpha, was found to be 0.84. The questionnaires were distributed by the researcher using Google Forms, and to ensure 100% return, they were then collected. The frequency distribution analysis and the percentage of responses provided by the teachers to each item were used to analyze the data. The results were also tallied up and collected in order to provide answers to the research question.